A quality classification of building stones from P-wave velocity and its application to stone cutting with gang saws - Synopsis - S. Kahraman (The Southern African Institute of Mining and Metallurgy, 2007)
P-wave velocity measurements were carried out on 22 large limestone blocks in a stone processing plant. In the laboratory, P-wave velocity of core samples was measured to obtain intact rock velocity. The square root of the ratio of the velocity of the large stone block to the velocity of the core specimen was called the velocity ratio index (VRI) and a quality classification for large building stones was suggested. In addition, the applicability of the established classification to stone cutting with gang saws was checked. It was concluded that the quality classification and estimation of slab production efficiency of the building stones can easily be made by ultrasonic measurements. However, the study was carried out only in limestone. Further study must be conducted to check the validity of the obtained results for the other rock types.